Eclectic Contexts of Xenophobic Workplace Discrimination in Post-apartheid South Africa - Duma, Vusumzi; Kang'ethe, Simon Murote (Research in Social Sciences and Technology, 2025)
Today, a fresher look at social structures shows that the possibility of living in a socially homogeneous society has lost its credibility. When any workplace is considered, migrant workers are exposed to both intended and unintended forms of xenophobic workplace discrimination daily in many migrant-receiving countries. Xenophobic workplace discrimination has pernicious and ramifying consequences for migrant workers. This article uses a review of the literature methodology. Xenophobic-driven workplace discrimination towards migrant workers in the workplace may manifest itself through the following forms: institutional discrimination at work, wage discrimination, discriminatory assignment to hazardous jobs, and discriminatory assignment to precarious and ‘ghettoized’ jobs. Because in the post-apartheid South African context, it is black African migrants who bear the brunt of xenophobic-driven workplace discrimination, these researchers recommend that: firstly, workplace ethics regulating the employment of labour migrants in the post-apartheid context should be guided by Article 1 of the ILO‟s (International Labour Organisation) Convention Discrimination (Employment and Occupation) of 1958. Trade union federations should utilise their bargaining power to shield migrant workers from forms of workplace discrimination that are xenophobically driven. Finally, the contribution of migrant workers, who are often victims of xenophobic-driven workplace discrimination, constitutes a significant economic dividend that could benefit the country’s economic productivity and growth. For this reason, it is of paramount importance for the government, business, and labour to collectively work together to eradicate the scourge of xenophobia as a form of discrimination in the workplace.